Antibacterial effect of Ag nanoparticles into the paper coatings - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE (WALTER DE GRUYTER GMBH, 2019)
Food packaging is the most important output of the printing industry. Giving antibacterial effect to the papers used in food packaging will extend the shelf life of the product and food transfer in healthier conditions. The nanoparticles with known antibacterial activity are nanosilver, nanogold, nanosilica. Binders used in paper coating provide a good nutrient medium for bacteria. In this study, Ag nanoparticles was first synthesized as monodisperse in 10 nm size with polyvinyl pyrrolidone and sodium boron reaction which will give antibacterial properties to paper coatings. The chemical structure of the synthesized Ag nanoparticles is illuminated by fourier transform infrared spectrophotometer (FTIR). Different paper coating formulations containing varying amounts of Ag nanoparticles were prepared with starch binder. Using these mixtures; papers coated with a laboratory-type paper coating machine onto 80 g/m(2) paper. Color, gloss, contact angle, surface energy, antibacterial properties of the paper against the E. coli bacteria and S. aureus bacteria were examined. As a result, Ag nanoparticles has been successfully synthesized and used in paper coating. Antibacterial and printability properties were improved by increasing the amount of Ag nanoparticles.
Keywords: Ag nanoparticles; antibacterial paper; E. coli; paper coating; S. aureus; MECHANICAL-PROPERTIES; SILVER; BIOSYNTHESIS; NANOTECHNOLOGY; RESISTANCE; EFFICACY; MELAMINE; EXTRACT